Analyzing a single-laser repumping scheme for efficient loading of a strontium magneto-optical trap - Hu, Fachao; Nosske, Ingo; Couturier, Luc; Tan, Canzhu; Qiao, Chang; Chen, Peng; Jiang, Yuhai; Zhu, Bing; Weidemüller, Matthias (Physical review, 2019)
We demonstrate enhanced loading of strontium atoms into a magneto-optical trap using a repumping scheme from the metastable state via the doubly excited state 5s5p P-3(2) -> 5p(2) P-3(2) at 481 nm. The number of trapped atoms is increased by an order of magnitude. The frequency and intensity dependence of the atom number enhancement, with respect to the nonrepumping case, is well reproduced by a simple rate equation model, which also describes single-laser repumping schemes reported previously. The repumping scheme is limited by a weak additional loss channel into the long-lived 5s5p P-3(0) state. For low repumping intensities, the signature of a halo formed by magnetically trapped atoms in the metastable state is found.
Gesehen am 30.07.2019